?Those Who Need It the Most?: Equity Framing in 2021 U.S. Print News About Food Assistance (Mary Ann Liebert, 2023)
Objective: To understand how equity appeared in news about food assistance from 2021. Methods: We assessed a national sample of news articles (N=298) for equity arguments and language about racial and health equity. Results: Only 28% of coverage argued that food assistance programs promote equity. Just 6% mentioned people of color or named racial disparities in food access. Discussion: Narratives that explain how food assistance programs reduce inequities could deepen their policy appeal and broaden public perceptions around recipients. Health Equity Implications: There are opportunities for news coverage to expand the discussion of how food assistance programs improve racial and health equity outcomes.